The Hyaluronan Pericellular Coat and Cold Atmospheric Plasma Treatment of Cells - Claudia Bergemann; Anna-Christin Waldner; Steffen Emmert; J. Barbara Nebe (Applied Sciences, 2020)
In different tumors, high amounts of hyaluronan (HA) are correlated with tumor progression. Therefore, new tumor therapy strategies are targeting HA production and degradation. In plasma medicine research, antiproliferative and apoptosis-inducing effects on tumor cells were observed using cold atmospheric plasma (CAP) or plasma-activated media (PAM). Until now, the influence of PAM on the HA pericellular coat has not been the focus of research. PAM was generated by argon-plasma treatment of Dulbecco’s modified Eagle’s Medium via the kINPen®09 plasma jet. The HA expression on PAM-treated HaCaT cells was determined by flow cytometry and confocal laser scanning microscopy. Changes in the adhesion behavior of vital cells in PAM were observed by impedance measurement using the xCELLigence system. We found that PAM treatment impaired the HA pericellular coat of HaCaT cells. The time-dependent adhesion was impressively diminished. However, a disturbed HA coat alone was not the reason for the inhibition of cell adhesion because cells enzymatically treated with HAdase did not lose their adhesion capacity completely. Here, we showed for the first time that the plasma-activated medium (PAM) was able to influence the HA pericellular coat.